The Tango of Problem Formulation: A Patient's/Researcher's Reflection on an Action Design Research Journey - Twomey, Michael B; Sammon, David; Nagle, Tadhg (JMIR Publications, 2020)
This paper reports on the reflection of the lead researcher, a 48-year-old patient with cystic fibrosis (CF), and aims to portray his real-life experience of a 10-month action design research (ADR) project. Playing a dual role, as both a patient and researcher, the lead researcher reflects deeply on his ADR experience with particular emphasis on the problem formulation stage of creating a simple yet impactful checklist to aid memory recall of CF patients or caregivers during a medical appointment. Using Driscoll's model of reflection, a real-life unsanitized ADR experience is carefully imparted via a series of 4 vignettes, including 4 key learnings, which highlight the connection between a meticulous considered approach to problem formulation and truly effective outcomes. By providing this rich account of problem formulation within ADR, it is hoped that this reflection will help researchers to better understand the complexity of problem formulation in design-oriented research; to avoid making assumptions and becoming fixated on solutions; and to move instead to an end point where several possible ways of examining a problem have been considered, explored, and understood-an end point where successful end results are reached through grit and determination. This paper advocates for the inclusion and portrayal of the actual realities or ups and downs of this dynamic and evolving stage of ADR, capturing the often-tacit knowledge of problem formulation and begetting a sense of realism and humanity to ADR serving as knowledge contributions in their own right. The lead researcher is the patient and researcher in this ADR project. This is my story!